The Impact of Rupiah Exchange Rate Depreciation on Foreign Exchange Difference Expenses and Financial Performance of Pharmaceutical Manufacturing Companies Listed on the Indonesia Stock Exchange - Agriend S. Putra; Adi Putra (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
The depreciation of the Rupiah exchange rate against foreign currencies, particularly the United States Dollar (USD), is one of the most significant market risks for the manufacturing industry sector in Indonesia. This study aims to analyze the impact of Rupiah exchange rate depreciation on foreign exchange expenses and the financial performance of pharmaceutical manufacturing companies listed on the Indonesia Stock Exchange (IDX). The national pharmaceutical industry has unique characteristics that are highly vulnerable to exchange rate fluctuations, considering that approximately 85% to 90% of active pharmaceutical ingredients are still supplied through import mechanisms. The research method used is a causal quantitative method with secondary data in the form of annual financial reports of pharmaceutical companies listed on the IDX. Financial performance in this study is measured using profitability ratios, such as Return on Assets (ROA) and Return on Equity (ROE), as well as operational efficiency ratios. The results of the panel data regression analysis indicate that Rupiah exchange rate depreciation has a significant positive effect on the surge in foreign exchange difference expenses. This increase in foreign exchange expenses is subsequently proven to have a significant negative impact on the company's ROA and ROE. The dual pressures of rising imported input costs and restrictions on domestic selling price adjustments (due to health insurance drug pricing regulations) have drastically eroded companies' net profit margins. These findings imply the importance of implementing more aggressive foreign exchange risk management strategies, such as hedging through forward derivative instruments or options, to maintain the financial stability of the national healthcare sector amidst global macroeconomic uncertainty.